IMPLEMENTASI BUKU DIGITAL DALAM MENGOPTIMALKAN PENGUNAAN LITERASI UNTUK MENYONGSONG REVOLUSI INDUSTRI 4.0 DI DALAM SEKOLAH - Syawaludin, Muhammad (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Development of communication information technology has transformed learning methods in the era of industrial revolution 4.0. One form ofdevelopmentin communication information technology is the use if digital book. Digital book can be one solution to fostering a culture of literacy in the world of education in particular, and Indonesia society in general. With a various advantages and appeal of digital book is expected to be able to foster interest in reading so that the literacy skills of the Indonesia people are increasing.So the literacy culture will more grow.